2007
DOI: 10.1021/bi700735t
|View full text |Cite
|
Sign up to set email alerts
|

TPR-Mediated Self-Association of Plant SGT1

Abstract: The tetratricopeptide repeat (TPR) domain mediates inter-protein associations in a number of systems. The domain is also thought to mediate oligomerization of some proteins, but this has remained controversial, with conflicting data appearing in the literature. By way of investigating such TPR-mediated self-associations we used a variety of biophysical techniques to characterize purified recombinant Sgt1, a TPR-containing protein found in all eukaryotes that is involved in a broad range of biological processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
5
40
0
Order By: Relevance
“…These data support the idea that SGT1 may form higher order oligomers. Consistent with such a model, we recently described how plant SGT1 forms a TPR-mediated dimer that increases the stability of the protein in vitro (Nyarko et al, 2007).…”
Section: Cs and Sgs Domains Are Required For Rx Resistancementioning
confidence: 60%
“…These data support the idea that SGT1 may form higher order oligomers. Consistent with such a model, we recently described how plant SGT1 forms a TPR-mediated dimer that increases the stability of the protein in vitro (Nyarko et al, 2007).…”
Section: Cs and Sgs Domains Are Required For Rx Resistancementioning
confidence: 60%
“…The self-association of AIP is very likely mediated by the TPR domain, as demonstrated for other TPR-containing proteins (Das et al 1998, Taylor et al 2001, Nyarko et al 2007). This suggests that AIP can homodimerise without the association of other auxiliary proteins or at least others than AhR or hsp90 and also that more than one molecule of AIP could be present in the AhR complex.…”
Section: Aip-hsc70mentioning
confidence: 77%
“…If these ratios are correct, the authors suggested that the multimeric complexes of AIP act as a reservoir able to regulate the amount of available monomeric AIP that can be included into the AhR complex or maybe in the other complexes with which AIP has been shown to interact. Furthermore, the TPR-mediated self-association of AIP might be a mechanism to specifically regulate its biological functions, as reported for the TPR-containing proteins PP5 and Sgt1 (Yang et al 2005, Nyarko et al 2007. For example, the phosphatase activity of PP5 is suppressed by an autoinhibited conformation maintained by the TPR domaincatalytic domain interaction (Yang et al 2005).…”
Section: Aip-hsc70mentioning
confidence: 81%
“…Moreover, nApc7 was found to form a dimer in solution. This homodimerization via its N-terminal dimerization motif is the first example of homodimerization that is mediated by the N terminus of TPR protein, although the TPR motif is known to mediate self-association for many TPRcontaining proteins, such as OGT (40), Tom70p (41), and SGT (42).…”
Section: Discussionmentioning
confidence: 99%